2016
DOI: 10.4081/dr.2016.6599
|View full text |Cite
|
Sign up to set email alerts
|

Erythrodermic psoriasis treated with apremilast

Abstract: Erythroderma is a rare potentially deadly exfoliative dermatitis characterized by diffuse cutaneous erythema which may be associated with multi-organ dysfunction. Therefore, it is imperative to recognize and treat it promptly. Erythrodermic psoriasis is the most common form of erythroderma. Management of this condition is largely based on aggressive supportive care and the use of anti-inflammatory immunosuppressive and biologic agents. We describe a case of psoriatic erythroderma which was triggered by withdra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Apremilast could be a potential choose for the nail psoriasis, scalp psoriasis, generalized pustular psoriasis, palmoplantar psoriasis, and erythrodermic psoriasis (Arcilla et al, ; Bissonnette et al, ; Jeon et al, ; Kushwaha, Repka, & Narasimha Murthy, ; Nguyen et al, ). There are only a case reported that apremilast was safe and efficacy for pediatric psoriasis (Smith, ), therefore, more evidence is expected.…”
Section: Small Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Apremilast could be a potential choose for the nail psoriasis, scalp psoriasis, generalized pustular psoriasis, palmoplantar psoriasis, and erythrodermic psoriasis (Arcilla et al, ; Bissonnette et al, ; Jeon et al, ; Kushwaha, Repka, & Narasimha Murthy, ; Nguyen et al, ). There are only a case reported that apremilast was safe and efficacy for pediatric psoriasis (Smith, ), therefore, more evidence is expected.…”
Section: Small Moleculesmentioning
confidence: 99%
“…The safety and efficacy of apremilast in psoriasis had been conducted in two multicenter, randomized, double blind, placebo-controlled trials, in which 31.7% apremilast patients achieved PASI75 versus 5.5% placebo patients at 16 weeks (Papp et al, 2015;Paul et al, 2015). Apremilast could be a potential choose for the nail psoriasis, scalp psoriasis, generalized pustular psoriasis, palmoplantar psoriasis, and erythrodermic psoriasis (Arcilla et al, 2016;Bissonnette et al, 2017;Jeon et al, 2017;Kushwaha, Repka, & Narasimha Murthy, 2017;Nguyen et al, 2016). There are only a case reported that apremilast was safe and efficacy for pediatric psoriasis (Smith, 2016), therefore, more evidence is expected.…”
Section: Pde4 Inhibitor For Treatment Of Psoriasismentioning
confidence: 99%
“…Apremilast has not been studied for the management of stable or unstable EP. There is one case of EP with significant systemic inflammatory response requiring inpatient admission that improved after 10 days of apremilast, but it had to be stopped due to development of atrial fibrillation, and the patient was switched to cyclosporine 4. There is another case of nearly EP flare in a patient with psoriasis for 25 years, due to discontinuation of adalimumab while on treatment for latent tuberculosis (TB), that responded well to apremilast 5.…”
Section: Introductionmentioning
confidence: 99%
“…There is only one case report in the literature where apremilast showed fast response in erythrodermic psoriasis but was early discontinued due to cardiologic issues. 4…”
Section: Introductionmentioning
confidence: 99%